Painting in a State of Exception : New Figuration in Argentina, 1960-1965 - Frank, Patrick, 1953- (Book collections on Project MUSE., 2016)
This book is a careful study of the four artists at the heart of the Nueva Figueracion postwar art movement, combining analyses of the artists' paintings with discussions of the social, political and artistic contexts in which they were created.